2022
DOI: 10.1111/ddi.13532
|View full text |Cite
|
Sign up to set email alerts
|

Flying insect biomass is negatively associated with urban cover in surrounding landscapes

Abstract: Aim In this study, we assessed the importance of local‐ to landscape‐scale effects of land cover and land use on flying insect biomass. Location Denmark and parts of Germany. Methods We used rooftop‐mounted car nets in a citizen science project (“InsectMobile”) to allow for large‐scale geographic sampling of flying insects. Volunteers sampled insects along 278 five‐km routes in urban, farmland, grassland, wetland and forest landscapes in the summer of 2018. The bulk insect samples were dried overnight to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(64 reference statements)
0
5
1
Order By: Relevance
“…Urbanisation as a process of sprawling cities with effects on land cover change, fragmentation, temperature and soil sealing, however, continues across the globe and is therefore an increasingly important threat (Grimm et al, 2008; Pickett et al, 2011). In contrast to our previous study, we found no evidence for an effect of farmland cover on biomass with an additional sampling year; however, the effect found in our previous study was weaker and more sensitive to analytical decisions than the effect of urban cover (Svenningsen et al, 2022).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Urbanisation as a process of sprawling cities with effects on land cover change, fragmentation, temperature and soil sealing, however, continues across the globe and is therefore an increasingly important threat (Grimm et al, 2008; Pickett et al, 2011). In contrast to our previous study, we found no evidence for an effect of farmland cover on biomass with an additional sampling year; however, the effect found in our previous study was weaker and more sensitive to analytical decisions than the effect of urban cover (Svenningsen et al, 2022).…”
Section: Resultscontrasting
confidence: 99%
“…Here, we extend our previous work (Svenningsen et al, 2022) to compare the impacts of urban and farmland covers on insect richness, biomass and evenness. Additionally, our new analysis included an additional sampling year.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Many works indicate a homogenisation and decrease in functional type, species diversity and/or insect abundance as urban density increases (in this SI see: Barao et al, 2024;Casanelles-Abella et al, 2024;Federico et al, 2024;Rivest & Kharouba, 2024;Sanetra et al, 2024;Svenningsen et al, 2024). This picture is, however, nuanced (e.g., Ancillotto & Rocco, 2024;Federico et al, 2024;Ombugadu et al, 2024) and although urban areas can detrimentally impact some insect taxa through the predominance of artificial environments, constrained habitats and disturbances, other taxa can adapt and thrive in the mosaic of semi-natural and novel environments, management variation and abundant resources (Curry et al, 2024;Hill et al, 2024;Nunes et al, 2024;Plummer et al, 2024;Xu et al, 2024).…”
Section: In Summarymentioning
confidence: 99%